The Influence of Lifestyle and Financial Literacy on Financial Behavior in Management Study Program Students Universitas Pembangunan Panca Budi - Sutrisno, Ayu; Aulia, (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to examine the effect of lifestyle and financial literacy on student financial behavior. The analysis technique used is associative analysis, this research applies quantitative methods. The sampling method for this study used random sampling techniques. The total population in this study consisted of active students of the Management Study Program at Universitas Pembangunan Panca Budi in the 2021-2023 stipulation year, totaling 952 respondents, with a sample of 90 samples taken. The data used in this study are primary data obtained through a digital questionnaire. The data testing media used in this research is IMB SPSS Version 27 software. The findings of this study indicate that lifestyle has a significant negative effect on financial behavior, while financial literacy has a significant positive effect on financial behavior. The resulting coefficient of determination shows that 32.5% of students' financial behavior is influenced by lifestyle and financial literacy variables, while the remaining 67.5% is influenced by other factors not examined in this study.